PENANGANAN KORUPSI BERDASARKAN HUKUM ADMINISTRASI NEGARA - Salwaa Pramiltari Annisa; Lukman Yudho Prakoso (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
Eliminating deficiencies and fraud is the goal of Indonesia's national development strategy. Authorities, civil servants, social organizations, and others are trying hard to overcome both "deficiencies" and "fraud." With limited budget and expertise, planned efforts must be carried out as effectively and efficiently as possible. The focus of this research is recording positive law, which is a foreword activity for each aspect of the research. The purpose of this research is to evaluate basic understanding of the current criminal legal system. This research uses a normative approach, which means that legal material is collected through methods of recognizing and recording both primary and inferior legal material. According to state administrative law, the strategy to eradicate corruption includes several elements of change, such as good leadership and state; audience programs, where these changes will reduce incentives to bribe, reduce the number of businesses, and give the public more opportunities to obtain audience services; correction by the ruling government, where this change is intended to reduce the number of companies operating, and increase people's opportunities to get public services.